Novel iron chelator SK4 demonstrates cytotoxicity in a range of tumour derived cell lines - Abdelaal, Gina; Carter, Andrew; Panayiotides, Mihalis I.; Tetard, David; Veuger, Stephany (Frontiers in Molecular Biosciences, 2022)
Iron is an essential micronutrient due to its involvement in many cellular processes including DNA replication and OXPHOS. Tumors overexpress iron metabolism linked proteins which allow for iron accumulation driving high levels of proliferation. Our group has designed novel iron chelator SK4 which targets cancer’s “iron addiction”. SK4 comprises of two key moieties: an iron chelation moiety responsible for cytotoxicity and an amino acid moiety which allows entry through amino acid transporter LAT1. We selected LAT1 as a route of entry as it is commonly overexpressed in malignant tumors. SK4 has previously demonstrated promising results in an in vitro model for melanoma. We hypothesized SK4 would be effective against a range of tumor types. We have screened a panel of tumor-derived cell lines from different origins including breast, prostate, ovarian and cervical cancer for SK4 sensitivity and we have found a range of differential sensitivities varying from 111.3μM to >500μM. We validated the iron chelation moiety as responsible for inducing cytotoxicity through control compounds; each lacking a key moiety. Following the screen, we conducted a series of assays to elucidate the mechanism of action behind SK4 cytotoxicity. SK4 was shown to induce apoptosis in triple negative breast cancer cell line MDA MB 231 but not ovarian cancer cell line SKOV3 suggesting SK4 may induce different modes of cell death in each cell line. As MDA MB 231 cells harbor a mutation in p53, we conclude SK4 is capable of inducing apoptosis in a p53-independent manner. SK4 upregulated NDRG1 expression in MDA MB 231 and SKOV3 cells. Interestingly, knockdown of NDRG1 antagonized SK4 in MDA MB 231 cells but not SKOV3 cells suggesting SK4’s mechanism of action may be mediated through NDRG1 in MDA MB 231 cells. In conclusion, we have shown tagging iron chelators with an amino acid moiety to allow entry through the LAT1 transporter represents a double pronged approach to cancer therapy, targeting “iron addiction” and amino acid metabolism dysregulation.